The concept of marketing efficiency, applications and policy implications: A case of dairy marketing in Addis Ababa, Ethiopia - Mbogoh, S.G. (1992)
The major concern of this study was to assess the relative efficiency of alternative marketing systems for dairy products. A number of partial efficiency criteria were developed. These partial efficiency criteria formed the basis from which the merit and demerits of the alternative marketing systems for liquid milk in Addis Ababa were assessed. The results of the study indicate that the rating of the performance of alternative marketing systems varies depending on the type of criterion used in the assessment of market performance. Hence there is no single organizational structure for dairy marketing systems that can be said to be unique in terms of economic performance. Hence there is need to evaluate local conditions and establish appropriate marketing systems to accompany dairy development projects in different countries. Apparently, any marketing system that can be said to be staisfactory should direct particular attention to meeting (1) customers convenience when collecting the product, (2) regularity and reliability of supply and (3) clean and hygienic premises from which the product is sold. And a mix of private and government dairy marketing systems would appear to perform better than government marketing systems alone Private marketing system appear to perform better in most cases.